2014
DOI: 10.3109/14756366.2013.866659
|View full text |Cite
|
Sign up to set email alerts
|

Novel phenolic inhibitors of the sarco/endoplasmic reticulum calcium ATPase: identification and characterization by quantitative structure–activity relationship modeling and virtual screening

Abstract: Inhibitors of the sarco/endoplasmic reticulum calcium ATPase (SERCA) are valuable research tools and hold promise as a new generation of anti-prostate cancer agents. Based on previously determined potencies of phenolic SERCA inhibitors, we created quantitative structure-activity relationship (QSAR) models using three independent development strategies. The obtained QSAR models facilitated virtual screens of several commercial compound collections for novel inhibitors. Sixteen compounds were subsequently evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Regarding study design, we sought to investigate if the publications fit into a broad categorization of the in silico strategies. We found that most studies solely used computational methods without further testing their findings in other scientific settings (46.64%) (Shah et al, 2012;Abazeed et al, 2013;Ain et al, 2013;Eichhorn et al, 2013;Emig et al, 2013;Leung et al, 2013;Liu et al, 2013Liu et al, , 2020Liu et al, , 2021Menden et al, 2013;Naresh et al, 2013;Omotuyi et al, 2013;Singh et al, 2013;Chen, 2014;Dean et al, 2014;Xu and Wang, 2014;Chuang et al, 2015;Dunna et al, 2015;Gustafson et al, 2015;Hammad and Azam, 2015;Kaur et al, 2015;Paula et al, 2015;Rubio-Perez et al, 2015;Sarvagalla et al, 2015;Zhang et al, 2015;Brown et al, 2016;Gayvert et al, 2016;Lee et al, 2016;Shafique et al, 2016;Tan, 2016;Verma et al, 2016;Spiliotopoulos et al, 2017aSpiliotopoulos et al, , 2017bJadhav and Karuppayil, 2017;Kabir et al, 2017Kabir et al, , 2018Kabir et al, , 2019Khanam et al, 2017;Salentin et al, 2017;…”
Section: Results Of Individual Sources Of Evidence and Data Synthesismentioning
confidence: 99%
“…Regarding study design, we sought to investigate if the publications fit into a broad categorization of the in silico strategies. We found that most studies solely used computational methods without further testing their findings in other scientific settings (46.64%) (Shah et al, 2012;Abazeed et al, 2013;Ain et al, 2013;Eichhorn et al, 2013;Emig et al, 2013;Leung et al, 2013;Liu et al, 2013Liu et al, , 2020Liu et al, , 2021Menden et al, 2013;Naresh et al, 2013;Omotuyi et al, 2013;Singh et al, 2013;Chen, 2014;Dean et al, 2014;Xu and Wang, 2014;Chuang et al, 2015;Dunna et al, 2015;Gustafson et al, 2015;Hammad and Azam, 2015;Kaur et al, 2015;Paula et al, 2015;Rubio-Perez et al, 2015;Sarvagalla et al, 2015;Zhang et al, 2015;Brown et al, 2016;Gayvert et al, 2016;Lee et al, 2016;Shafique et al, 2016;Tan, 2016;Verma et al, 2016;Spiliotopoulos et al, 2017aSpiliotopoulos et al, , 2017bJadhav and Karuppayil, 2017;Kabir et al, 2017Kabir et al, , 2018Kabir et al, , 2019Khanam et al, 2017;Salentin et al, 2017;…”
Section: Results Of Individual Sources Of Evidence and Data Synthesismentioning
confidence: 99%
“…Nevertheless, in the meantime, novel SERCA-inhibiting hydroquinone and phenolic compounds were identified based on quantitative structure−activity relationship (QSAR) modeling. 166 Although the specificity of compound 2 as SERCA inhibitor is not absolute, recently, SERCA inhibitors 1 and 2 were also found to significantly increase the lifespan of Caenorhabditis elegans. 167 Particularly compound 2 as a reversible SERCA inhibitor, but also compound 1 as irreversible one, changed the lifespan in a bell-shaped concentration manner of both wild type and caloric restriction eat-2 mutant of C. elegans, highlighting the multipotentiality of calcium signaling modulation and the importance of its research.…”
Section: Non-terpenoid Serca Inhibitorsmentioning
confidence: 99%
“…Therefore, the effect of compound 2 studied in rat ventricular myocytes is not surely SERCA-specific. It remains to be elucidated if derivatization of the compound 2 structure could resolve this issue. Nevertheless, in the meantime, novel SERCA-inhibiting hydroquinone and phenolic compounds were identified based on quantitative structure–activity relationship (QSAR) modeling …”
Section: Non-terpenoid Serca Inhibitorsmentioning
confidence: 99%
“…Regarding study design, we sought to investigate if the publications fit into a broad categorization of the in silico strategies. We found that most studies solely used computational methods without further testing their findings in other scientific settings (46.64%) (Shah et al, 2012;Abazeed et al, 2013;Ain et al, 2013;Eichhorn et al, 2013;Emig et al, 2013;Leung et al, 2013;Liu et al, 2013Liu et al, , 2020Liu et al, , 2021Menden et al, 2013;Naresh et al, 2013;Omotuyi et al, 2013;Singh et al, 2013;Chen, 2014;Dean et al, 2014;Xu and Wang, 2014;Chuang et al, 2015;Dunna et al, 2015;Gustafson et al, 2015;Hammad and Azam, 2015;Kaur et al, 2015;Paula et al, 2015;Rubio-Perez et al, 2015;Sarvagalla et al, 2015;Zhang et al, 2015;Brown et al, 2016;Gayvert et al, 2016;Lee et al, 2016;Shafique et al, 2016;Tan, 2016;Verma et al, 2016;Spiliotopoulos et al, 2017aSpiliotopoulos et al, , 2017bJadhav and Karuppayil, 2017;Kabir et al, 2017Kabir et al, , 2018Kabir et al, , 2019Khanam et al, 2017;Salentin et al, 2017;…”
Section: Results Of Individual Sources Of Evidence and Data Synthesismentioning
confidence: 99%